Histological and Histochemical Studies of the Eye Structure of Anas Platyrhynchus (Mallard) Duck Species - Waleed J. A. Al-Kelaby; Zahraa S. M. Al Kaabi; Hany A. Alhussaniy (The Indian Veterinary Journal, 2024)
The aim of the present study is to describe the histological features of the eyes of a domestic mallard duck, Anasplatyrhynchus. The eyeballs often adult males and females constituted the material of the study. The cornea histologically consisted of a stroma, a Descemet membrane, a bowman membrane, an external epithelium, and a posterior epithelium. The choroid, located between the sclera and the retina and begins from the ciliary body to the optic nerve, is rich in blood vessels. The four histological layers of the choroid were suprachoroidea, brushes membrane, vascular layer, and choriocapillaris. The ciliary body connected anteriorly to the eye and was the front portion of the choroid. Two layers comprise the ciliary processes' epithelium: a shallow, cuboidal, nonpigmented layer and a deep, strongly pigmented one. Hyaline cartilage serves as the support of the ciliary body in addition to the fibers of smooth muscle. The retinaconsists of ten layers. The choroid, composed of four layers (suprachoroidal, bloodvessel layers, tapetum fibrosum, and choriocapillaris), is one of the five components of the cornea. Ten layers make up the sensitive portion of the retina.